Development of Electrical Lighting Installation Jobsheet at SMKN 4 Kota Serang - Prestanty, Deva Adelya; Wardoyo, Siswo; Fatkhurrokhman, Mohammad (The Future of Education Journal, 2025)
This study aims to produce an electrical lighting installation jobsheet, in order to determine the level of feasibility and effectiveness in learning activities at SMKN 4 Kota Serang. This study uses the Research and Development (R&D) research method. This study conducted a feasibility test with media expert validation obtaining an average score of 3.83 in the "very valid" category, for material experts with an average score of 3.84 in the "very valid" category, and for user responses with an average score of 3.49 in the "very valid" category. A competency test was conducted on students to determine the level of effectiveness, where the results of the diagnostic assessment obtained 0% with the "very low" success criteria, the formative assessment reached 95.83% with the "very high" success criteria, the results of the summative assessment of students were 82.6% with the "high" success criteria, and for the effectiveness of the jobsheet in the learning process was 0.72 with the "high effectiveness" category.